Patient-Centered and Visual Quality Outcomes of Premium Cataract Surgery: A Systematic Review. Issue 4 (26th June 2017) - Wang, Sophia Y.; Stem, Maxwell S.; Oren, Gale; Shtein, Roni; Lichter, Paul R.
Purpose: Over 8 million cataract surgeries are performed in the United States and the European Union annually, with many patients choosing to pay out of pocket for premium options including premium intraocular lens implants (IOLs) or laser-assisted cataract surgery (LACS). This report provides a systematic review evaluating patient-centered and visual quality outcomes comparing standard monofocal IOLs to premium cataract surgery options. Methods: PubMed and EMBASE were searched for publications published between January 1, 1980, and September 18, 2016, on multifocal, accommodative, and toric IOLs, monovision, and LACS, which reported on 1) dysphotopsias, 2) contrast sensitivity, 3) spectacle independence, 4) vision-related quality of life or patient satisfaction, and 5) IOL exchange. Results: Multifocal lenses achieved higher rates of spectacle independence compared to monofocal lenses but also had higher reported frequency of dysphotopsia and worse contrast sensitivity, especially with low light or glare. Accommodative lenses were not associated with reduced contrast sensitivity or more dysphotopsia but had only modest improvements in spectacle independence compared to monofocal lenses. Studies of monovision did not target a sufficiently myopic outcome in the near-vision eye to achieve the full potential for spectacle independence. Patients reported high levels of overall satisfaction regardless of implanted IOL. No studies correlated patient-reported outcomes with patient expectations. Conclusions: Studies are needed to thoroughly compare patient-reported outcomes with concomitant patient expectations. In light of the substantial patient costs for premium options, patients and their surgeons will benefit from a better understanding of which surgical options best meet patients' expectations and how those expectations can be impacted by premium versus monofocal—including monovision—options.